Transformation of features of national mentality in the chumak song (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
In the article the author discovers and systematizes traditions and signs of national mentality in chumack’s folklore. The analysis of chumack’s songs gives the opportunity to organize the conception of psychological type of chumack.
Keywords: folklore; chumack’s; song